Quasi-static cyclic tests on a half-scaled two-storey steel frame equipped with Crescent Shaped Braces at both storeys: Experimental vs. numerical response. (15th December 2022) - Mokhtari, Elnaz; Palermo, Michele; Laghi, Vittoria; Incerti, Andrea; Mazzotti, Claudio; Silvestri, Stefano
Abstract: This paper discusses the results of quasi-static cyclic tests performed on a half-scaled two-storey one-bay steel pendular frame equipped with Crescent Shaped Braces (CSBs) at both storeys. The same steel pendular frame was previously tested with only one brace located at the first storey to validate the structural response of a single device when inserted into a realistic frame. The experimental results of this first configuration were presented and discussed in a companion paper which proved that the experimental behaviour of the single CSB matched the theoretical predictions and that the effect of connection plates is not negligible. Here the attention is focused, for the first time, on a structure fully braced along the height by CSBs as in a realistic building configuration. During the tests, the global and local responses of the structure were monitored by means of inductive displacement transducers, strain gauges and Digital Image Correlation technique. Non-linear Finite Element models were also developed to provide an in-depth interpretation of the experimental results. The objective is twofold: (i) the experimental assessment of the global performances of the braced structure in terms of stiffness, strength, ductility and energy dissipation, and (ii) the comparison between the experimental and the numerically-simulated response of the structure, with specific focus on the response of the two CSBs and on the effects of real connections (parasitic bending moments and bolt slippage). In conclusion, the results of the experimental test carried out on a two-storey building structure fully braced with CSBs proved that the CSB design procedure is effective and the use of CSBs as diagonal braces could represent a feasible solution for buildings to achieve multiple seismic performance objectives. Highlights: Two-storey steel pendular frame fully braced with Crescent Shaped Braces at both storeys. Quasi-static cyclic response recorded by displacement transducers, strain gauges, DIC technique. Experimental response compared with numerical response including non-linear behaviour of the connections. No damage under low-intensity earthquake input by providing the required initial elastic stiffness. Uniform along-the-height yielding and moderate energy dissipation for high-intensity earthquake input.